Predicting Yoga Performance: A Multiple Regression Analysis of Physical Fitness Variables - Shekhar Singh, Chandra; Sharma, Neelam (Journal of Neonatal Surgery, 2025)
This study examines the correlation between physical fitness variables and yogic performance in 25 young yogasana players from Delhi-NCR. Utilizing Pearson correlation and multiple linear regression analyses, the study identifies flexibility as a significant predictor of yogic performance, explaining 38.7% of its variance. Results indicate a strong positive correlation between flexibility and yogic performance (r = .622, p < 0.01), while sit-ups, push-ups, and balance show non-significant correlations. The findings highlight the critical role of flexibility in enhancing yoga performance, suggesting its incorporation into training regimens for improved outcomes. Future research should explore additional variables influencing yogic performance.